EFEK SITOTOKSIK DAN PEMACUAN APOPTOSIS FRAKSI PETROLEUM ETER EKSTRAK ETANOL DAUN TAPAK LIMAN (Elephantopus scaber Linn) TERHADAP SEL HELA - Yeni Listyowati; Nurkhasanah Nurkhasanah (Universitas Ahmad Dahlan, 2013)
Elephantopus scaber Linn. has been reported to have cytotoxic effects on breast cancer cells and thepotential to be developed as anticancer agent. This study aims was to determine the cytotoxic activity andapoptosis induction effect of petroleum ether fractions of ethanolic extract of (Elephantopus scaber Linn) leavesagainst cervical cancer cells (HeLa). Petroleum ether fraction was obtained by dissolving eyhanolic extract inpetroleum ether, and the soluble fraction was as petroleum ether fraction. The method used for cytotoxic activitytest was MTT test. The concentration series used were 2000; 1500; 1000; 800; 400; 200; 100; 50; 25; 12.5; 6.25and 3.125 mg/ml. The IC50 used as cytotoxic parameters. The apoptotic observations was conducted usingacridine orange and ethidium bromide. The study showed the IC50 of petroleum ether fraction of (Elephantopusscaber Linn) ethanolic extract was 185 ug/ml. The study also showed the potency to stimulate apoptosis in HeLacells.